DEVELOPING MULTIPLE INTELLIGENCES THROUGH ICT-BASED E-LEARNING PROGRAM - Mayub, Afrizal; Fahmizal, Fahmizal (Sanata Dharma University Yogyakarta, 2023)
This study aims to determine the development of nine types of intelligence (Multiple Intelligences) through an e-learning program implemented through a computer network and/or personal computer (PC) with CD ROM. This type of research includes quantitative descriptive research, which describes the function of e-learning programs as a means of growth and development of all types of intelligence. The research method is carried out by comparing the pedagogical way of developing multiple intelligences with the facilities owned by the e-learning program. The degree of conformity used a percentage (%), then processed using a Likert Scale. Based on theory and virtual experiments, as well as the opinions of 2 experts and 35 education practitioners as junior/high school teachers, it was found that the e-learning program functions to facilitate the development of intelligence in the